Sharon Tate a life - Sanders, Ed 1939- (Da Capo Press, 2015)
"In 1971, Ed Sanders published The Family, his insider's account of the Manson family murders; it was an immediate sensation. Using the same investigative skills and insider contacts that informed his counterculture classic, Sanders delivers the definitive account of the brief and tragic life of Sharon Tate. The biography takes a close look at Tate's life-from her itinerant childhood and early career in fashion to her transition to film, passionate marriage to the brilliant and troubled Roman Polanski, and violent murder at the hands of the Manson family cult. Sanders's Sharon Tate offers new insights into what happened on the night of her death and explores new motives for the targeting of the Polanski household. Illustrated with Rick Veitch's evocative images, Sharon Tate is required reading for anyone fascinated by the dark side of the '60s. "..